Analisis Penerapan Manajemen Waktu Pekerjaan Instalasi Listrik PT. Duta Bangun Sentosa dengan Metode Critical Path Method (CPM) pada Proyek Lampung City - Muhammad Jihaddien Daffa; Sukanta Sukanta (Peneliti.net, 2022)
Project implementation often occurs delays from the initial plan when the project plan is completed due to several factors. This problem also occurs in the construction of an apartment building and a mall which is being implemented by PT. Duta Bangun Sentosa which went slower than planned. To return the project's progress to the original plan, an effort to accelerate the duration of the project using the Critical Path Methode, this method is needed to find out the optimal critical path, time, and cost in the Lampung City Apartment Bay semi-basement project. This research uses direct observation to the project site to obtain data on work duration and costs. The results of the critical path in the Bay Mall and Lampung City Apartment semibasement project obtained the critical path for work A(1)→B(1)→C(2)→F(5)→I(5)→L(5)→ P(5)→Q(1)→R(1) with a total of 26 weeks of work at a cost of Rp. 3,732,000,000 (three billion seven hundred and thirty-two million rupiah). This result is an acceleration of the project from the initial plan of 32 weeks. Although it costs quite a lot, this project can reduce the duration of work to achieve the project target